Student-Centered Learning as a Factor in the Development of Foreign Language Competence in the Context of Integrated Instruction - Frumkina, Aryna (Pedagogical Discourse, 2025)
The article presents an analysis of student-centered learning environments as a determining factor in the development of foreign language competence among higher education students within the framework of integrated instruction. The methodological basis is a combination of theoretical and empirical methods. A content analysis of scientific sources on the problems of student-centered learning, psycholinguistics, cognitive linguistics, and foreign language teaching methods was carried out; the results of observation of educational practices within integrated courses were summarized and a qualitative interpretation of the effectiveness of those educational solutions that were tested in a real academic environment was carried out. The use of an integrated approach allowed not only to describe the phenomenon at the theoretical level, but also to substantiate its significance in the context of the formation of modern foreign language competence of higher education applicants. The study outlines psycholinguistic and methodological prerequisites that ensure productive language development through the combination of linguistic, cognitive, and creative components of the educational process. Special attention is paid to the mechanisms of dynamic stereotype formation, associative encoding, initiative-based language production, and speech self-regulation, which are activated through contextualized and personalized language activity. The effectiveness of integrated educational strategies is explored, particularly CLIL models, problem-based learning, reflective practices, visualization, digital tools, and project-based collaboration. The article substantiates the pedagogical value of combining subject content and language training within a unified educational space where the learner plays an active role in communicative interaction. It also describes the methodological features of student-centered environments, including flexible task structures, multimodal content delivery, open feedback systems, and a focus on interdisciplinary thinking. The materials can be used for designing academic components in the training of humanities specialists and may serve as a basis for further research or practical application in higher education teaching contexts.